CLINICAL UTILITY OF ULTRASONOGRAPHY BI-RADS IN THE EVALUATION OF BREAST CANCER IN PATIENTS WITH PALPABLE BREAST MASSES - Dr Sahil N. Shah; Dr Saloni N. Shah; Dr. Zarna Shah; Dr Vismit Gami; Dr Spruha Jhuvar; Dr Dev Desai (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Diagnosing and stage breast cancer with an easy and widely useable method that can be employed worldwide in the poorest and wealthiest settings is important. Mammography is a technique that might not be available in faraway clinics and it is technically challenging whereas USG can be available in most remote areas and small hospitals far from tertiary care hospitals. Even a trainee Radiology resident can use USG BIRADS and can be used diagnostically for that, it is important to define its, diagnostic accuracy with Sensitivity, Specificity and other diagnostic parameters. Aims: - To determine the Diagnostic accuracy of USG BIRADS compared to the gold standard Histopathology report Methodology A Retrospective cohort study was conducted at a tertiary care hospital. a total of 84 female patients presenting to Surgical OPD with complaints of a breast lump or pain were enrolled from their records. Their Breast USG results were analysed to correctly identify their BIRADS stage and then their corresponding Histopathology report was taken into account as the gold standard to compare the USG results against. Excel, SPSS and Revman were used to conduct analysis and create results. Results: - 36 of these 84 patients belonged to BIRADS 1, 2, and 5 where Sensitivity, Specificity and PPV were calculated at 100%. No one was diagnosed with BIRADS III from USG reports. For USG BIRADS 4, in total 48 patients Sensitivity was 0.667, specificity was 0.883, and PPV was 0.364. Conclusion: - Patients whose USG show Benign growth or can be diagnosed in BIRADS 1, 2, 3, and 5 can be counted as accurate and precise. When the USG diagnosis describes the patient to be in BIRADS 4, the sensitivity and PPV show poor results showing a very low probability of the patient being truly positive when the diagnosis gives a positive result.